Sistem Pakar Untuk Menentukan Penyakit Kucing Menggunakan Metode Certainty Factor - Saputro, Dedy Tri; Jusak, Jusak; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: Contagious cat disease is one type of disease that is often infecting cats. Contagious diseases are part of the disease that spread from saliva, feces, urine, cakaran, aerosols, and also indirectly to other cats and keepers. An infectious disease is caused by several factors, namely protozoa, viruses, bacteria and fungi, the effects of nutrients and the environment. In the absence of quickly and precise treatment, it will to lead to the transmission of the disease to other cats and people, worsely it can cause death cats. Based on the problems above, in this study, we develope an expert system that is able to assists in determining the cat diseases. Currently, there has not been any application for the dealing with identification of the diseases of cats. This expert system utilizes the certainty factor to determine any symptoms experienced by cats. The system will equalize with the existing rules. The system will provide decision of the cat's illness. Based on the experiment, it is evident that the expert system is able to determine cat diseases with accuracy of 93,3%. The results were obtained from testing of 15 tested cases done by vets. Keywords : Feline Diseases , Certainty Factor, Expert System